The impacts of the instructions of predicting and visualizing strategies on EFL learners' reading comprehension : - Trần, Thị Anh Đào (Can Tho University, 2015)
Impacts of the instructions of predicting and visualizing strategies on EFL learners' reading comprehensionThen given pedagogical implications and recommendations for future research were proposed in teaching and learning EFL reading